Asp271 is critical for substrate interaction with the surface binding site in β‐agarase a from Zobellia galactanivorans. Issue 1 (4th November 2018) - Wilkens, Casper; Tiwari, Manish K.; Webb, Helen; Jam, Murielle; Czjzek, Mirjam; Svensson, Birte
Abstract: In the marine environment agar degradation is assured by bacteria that contain large agarolytic systems with enzymes acting in various endo‐ and exo‐modes. Agarase A (AgaA) is an endo‐glycoside hydrolase of family 16 considered to initiate degradation of agarose. Agaro‐oligosaccharide binding at a unique surface binding site (SBS) in AgaA from Zobellia galactanivorans was investigated by computational methods in conjunction with a structure/sequence guided approach of site‐directed mutagenesis probed by surface plasmon resonance binding analysis of agaro‐oligosaccharides of DP 4‐10. The crystal structure has shown that agaro‐octaose interacts via H‐bonds and aromatic stacking along 7 subsites (L through R) of the SBS in the inactive catalytic nucleophile mutant AgaA‐E147S. D271 is centrally located in the extended SBS where it forms H‐bonds to galactose and 3, 6‐anhydrogalactose residues of agaro‐octaose at subsites O and P. We propose D271 is a key residue in ligand binding to the SBS. Thus AgaA‐E147S/D271A gave slightly decreasing K D values from 625 ± 118 to 468 ± 13 μM for agaro‐hexaose, ‐octaose, and ‐decaose, which represent 3‐ to 4‐fold reduced affinity compared with AgaA‐E147S. Molecular dynamics simulations and interaction analyses of AgaA‐E147S/D271A indicated disruption of an extended H‐bond network supporting that D271 is critical for the functional SBS. Notably, neither AgaA‐E147S/W87A nor AgaA‐E147S/W277A, designed to eliminate stacking with galactose residues at subsites O and Q, respectively, were produced in soluble form. W 87 and W277 may thus control correct folding and structural integrity of AgaA.